Patterns of care and outcomes for women with locally advanced cervical cancer, treated with curative intent, between 2013-2017 at a tertiary centre in South Africa - Maina, Juliet (Division of Radiology, 2025)
Objective Cervical cancer is the leading most common cause of cancer-related deaths in South Africa. The standard treatment guidelines of locally advanced cervical cancer (LACC) is external beam radiation followed by brachytherapy with concurrent platinum based chemotherapy. The aim of this study is to evaluate the patterns of care and outcomes for patients with LACC (Stage IB1 – IVA) treated with curative intent at a tertiary center in South Africa. Materials and Methods This is a retrospective study conducted at Groote Schuur Hospital (GSH) in Cape Town, South Africa between July 2013 – July 2017. Overall survival (OS) and disease free survival (DFS) were evaluated using the Kaplan–Meier method. Factors associated with outcomes were analyzed using Cox proportional hazards regression modeling. Logistic regression modeling was performed to assess factors associated with chemotherapy receipt and baseline hemoglobin ≥ 10 g/dL. Results A total of 278 women were eligible to participate in this study, of which 28.4% (n=79) were HIV infected and 71.6% (n=199) were HIV uninfected. Among the patients with HIV the median CD4 count was 441 cells/μL (IQR; 315-581 /μL) and all had been initiated ART before commencing treatment. The median age for all patients 51 years(IQR; 41-60). Most patients had stage II disease accounting for 48.6% (n=135) or stage III disease accounting for 45.3% (n=126). Majority of the patients had squamous cell carcinoma (SCC) 88.4% (n=246). Evaluation of baseline investigation showed median Hb for all patients was 11.3g/dL (IQR; 9.70-12.8). Patients who received concurrent chemotherapy were 64.8% (n=180) for a median of 5 cycles. Median EQD2 dose 74.5Gy (IQR;69-80.9). The 2-year OS and DFS in the entire population was 73.3% and 72.3% respectively. Factors associated with improved OS in our cohort were receipt of chemotherapy (HR 0.32, p=0.005) and higher baseline haemoglobin (HR 0.86; p=0.018). On multivariate logistic regression adjusting for age, stage, and HIV status, showed that patients with stage III/IV disease were less likely to receive chemotherapy (HR 48.17, p<0.001) and were less likely to have haemoglobin >=10g/dL (HR 0.20, p<0.001). The 2- year OS was 87.4% for patients who received concurrent chemoradiotherapy (CCRT) vs. 52.8% for those who received radiotherapy (RT) alone (p<0.001). The 2-year DFS was 80.2% for those who received CCRT vs 58.3% for those who received radiotherapy alone(p=<0.001). Conclusion Concurrent chemotherapy is significantly associated with increased survival. In this study, patients with stage III and IV treated with curative intent did not receive chemotherapy, which was detrimental to their survival. Therefore, if performance status allows, it is essential for all to receive chemotherapy. However, patients with low Hb may require transfusion to necessitate they receive chemotherapy.